Association between Dietary Vitamin A and HPV Infection in American Women: Data from NHANES 2003–2016. (10th January 2020) - Huang, Xian; Chen, Chi; Zhu, Fangfang; Zhang, Yingxuan; Feng, Qiuting; Li, Jingwei; Yu, Qingying; Zhong, Yanlan; Luo, Songping; Gao, Jie
Abstract : Objective . Evidence regarding the relationship between vitamin A and HPV infection was limited. Therefore, this study is designed to investigate whether vitamin A was independently related to HPV infection in 13412 American women from NHANES for seven cycles. Methods . The present study is a cross-sectional study. A total of 13412 eligible participants who had available HPV tests and vitamin A intake data were registered in the NHANE database from 2003 to 2016. The targeted independent variable and the dependent variable were vitamin A measured at baseline and HPV infection, respectively. We analyzed the association between dietary vitamin A intake and the prevalence of HPV infection. Besides, GAM and smooth curve fittings were used to address the nonlinear relationship between vitamin A and HPV infection to determine the effect of HPV infection. Results . The result of fully adjusted binary logistic regression showed vitamin A was not associated with the risk of HPV infection after adjusting confounders (odds ratio = 0.97, 95% confidence interval: 0.97–1.02). A nonlinear relationship was detected between vitamin A and HPV infection, whose inflection point was 10.5 of log2 vitamin A (by the recursive algorithm). One unit increase of log2 vitamin A is associated with the 10% reduced risk of HPV infection when dietary vitamin A is < 1448.155mcg. Conversely, when the dietary vitamin A intake is ≧1448.155 mcg, for each additional log2 of vitamin A, the risk of HPV infection increased by 70%. Conclusions . We found that dietary vitamin A was quite different from the trend of HPV infection in different confidence intervals. The results suggested that an appropriate amount (95% CI: 0.9–1.0, <10.5 of log2 transformer, i.e., 1448.155 mcg) of dietary vitamin A may be beneficial to prevent HPV infection. However, excessive intake of dietary vitamin A (95% CI: 1.1–2.8, ≧10.5 of log2 transformer, i.e., 1448.155 mcg) may increase the risk of HPV infection.